ANALISIS MOTIVASI DAN HASIL BELAJAR MATEMATIKA TERHADAP PEMBELAJARAN DARING PADA PESERTA DIDIK KELAS VII SMPN 5 KOTABARU - Muli Aprida; Muhammad Ali (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
This study aims to determine the motivation and learning outcomes of students in class VII SMPN 5 Kotabaru after the application of online learning. The method used in this research is descriptive research with a qualitative approach that utilizes qualitative data and is described descriptively. Descriptive research aims to create a systematic, factual and accurate description, description of the facts, properties and relationship between the phenomena be`ing investigated. The results showed that the learning motivation of class VII students at SMPN 5 Kotabaru was categorized as high with an average score of 77% ant the learning outcomes of grade VII students at SMPN 5 Kotabaru after online learning could be categorized as good with an average 69,17. Motivations to learn is not the main factor in determining learning outcomes, but learning motivation is important for increasing optimal learning outcomes. Keywords: Learning Motivation, Mathematics Learning Outcomes, Online Learning.